2021
DOI: 10.1017/dem.2021.21
|View full text |Cite
|
Sign up to set email alerts
|

Financial support by older adults to family members: a configurational perspective

Abstract: Most research on financial inter vivos transfers from older parents to their family members is focused on the giver–receiver dyad, usually between an older parent and an adult child. This study aimed to investigate older adults' financial support beyond this level of intergenerational dyads using an egocentric network perspective (i.e., the configurational approach). Data were from a sample of 2,991 older adults (aged 65 and older) from the Vivre/Leben/Vivere study, a large survey addressing family life and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Studies have shown some negative impacts of family investment on older adults' SWB (Choi et al, 2013;Huxhold et al, 2014;Ramia and Voicu, 2022). Overall, family ties involve more constraints (both as constrained and constraining) and seem more ambivalent than non-kin relationships regarding SWB issues: they can be simultaneously not just an important source of support but also a source of tension by reducing the autonomy of older individuals (Lüscher and Pillemer, 1998;Baeriswyl et al, 2022). However, our results establish a positive association between visiting family members and life satisfaction that underlines the emancipatory dimension of the family (Schwartz, 1990).…”
Section: Social Participations and Life Satisfactionmentioning
confidence: 99%
“…Studies have shown some negative impacts of family investment on older adults' SWB (Choi et al, 2013;Huxhold et al, 2014;Ramia and Voicu, 2022). Overall, family ties involve more constraints (both as constrained and constraining) and seem more ambivalent than non-kin relationships regarding SWB issues: they can be simultaneously not just an important source of support but also a source of tension by reducing the autonomy of older individuals (Lüscher and Pillemer, 1998;Baeriswyl et al, 2022). However, our results establish a positive association between visiting family members and life satisfaction that underlines the emancipatory dimension of the family (Schwartz, 1990).…”
Section: Social Participations and Life Satisfactionmentioning
confidence: 99%
“…Poverty‐related shame exacerbates social exclusion and reduces older adults’ self‐esteem, confidence and self‐perception (Walker et al, 2013). Many of the study's participants play an active role or are the main source of income in their immediate family, which could contribute to improving their self‐perception and mitigate the negative effects of poverty‐related shame (Baeriswyl et al, 2022). However, it is important to highlight that some of the older adults living in poverty have to ask for financial help from their families.…”
Section: Discussionmentioning
confidence: 99%